AKIBAT HUKUM TERHADAP MASYARAKAT YANG TIDAK MELAKUKAN PHYSICAL DISTANCING DALAM PENANGGULANGAN PENYEBARAN VIRUS CORONA - Syaiful Arif (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
AbstractThe spread of the Coronavirus in Indonesiahas become a national di-saster. The government is trying to overcome it by issuing a physical distancing policy. Physical distancing is a form of health quarantine, which is carried out by each individual to keep a distance between one another. However, the policy was not implemented properly due to lack of community legal awareness, so that those who violated the sanctions could be subjected. The regulation of physical dis-tancing as an effort to prevent the spread of the Corona virus in positive law in Indonesia is regulated in Article 9 of Law Number 6 Year 2018, which states that the obligation for each to comply with the implementation of health quarantine and participate in the administration health quarantine. The legal consequences for people who do not carry out physical distancing as an effort to prevent the spread of the Coronavirus in Indonesia are criminal sanctions in the form of imprisonment and/or criminal fines (Article 93 of Law Number 6 Year 2018), and if done or ordered by the controlling personnel corporation or corporate management, the penalty imposed is maximum imprisonment and maximum fine, each added with a weighting penalty of 2/3 (two-thirds), and the principal criminal imposed on the corporation is a maximum fine plus an offense of 2/3 (Article 94 of Law Number 6 the Year 2018). Keywords: Corona Virus, Legal Effects, Physical Distancing